2014
DOI: 10.1136/gutjnl-2013-306604
|View full text |Cite
|
Sign up to set email alerts
|

IL-26 is overexpressed in chronically HCV-infected patients and enhances TRAIL-mediated cytotoxicity and interferon production by human NK cells

Abstract: This study highlights IL-26 as a new player in the inflammatory and antiviral immune responses associated with chronic HCV infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
65
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 52 publications
(65 citation statements)
references
References 45 publications
0
65
0
Order By: Relevance
“…In addition to their evidence for antibacterial effects, Meller et al showed that IL-26 triggers the production of the antiviral cytokine interferon (IFN)-α (12,13) in plasmacytoid dendritic cells via activation of TLR9, by forming complexes with DNA from cells or from dying bacteria (12). Furthermore, the previous study by Miot et al also showed that IL-26 induces the production of the antiviral cytokines IFN-β and IFN-γ in NK cells in association with chronic HCV infections (7). Thus, IL-26 bears the potential to be involved in immune responses to both bacterial and viral stimulation.…”
Section: Interleukin-26 Production In Human Primary Bronchial Epithelmentioning
confidence: 91%
See 4 more Smart Citations
“…In addition to their evidence for antibacterial effects, Meller et al showed that IL-26 triggers the production of the antiviral cytokine interferon (IFN)-α (12,13) in plasmacytoid dendritic cells via activation of TLR9, by forming complexes with DNA from cells or from dying bacteria (12). Furthermore, the previous study by Miot et al also showed that IL-26 induces the production of the antiviral cytokines IFN-β and IFN-γ in NK cells in association with chronic HCV infections (7). Thus, IL-26 bears the potential to be involved in immune responses to both bacterial and viral stimulation.…”
Section: Interleukin-26 Production In Human Primary Bronchial Epithelmentioning
confidence: 91%
“…In the current study, in response to the tested viral stimuli is a strong indication of its involvement in pulmonary host defense against viral infections in the airways. This is particularly true given that IL-26 stimulates the production of antiviral cytokines including IFN-β and IFN-γ in NK cells during chronic HCV infections (7,13), as well as IFN-α in plasmacytoid dendritic cells in complex with DNA from dying bacteria and cells in vitro (12,13). Using IHC, we found a clear-cut expression of IL-26 protein in granulae and the cytoplasm of epithelial cells in bronchial tissue biopsy samples from healthy human subjects (with normal CRP levels).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations